GAIA Simulations of Electric Potential Variations in the Equatorial Evening Ionosphere after a Severe Solar Flare - Matsumura, Mitsuru; Shiokawa, Kazuo; Shinagawa, Hiroyuki; Otsuka, Yuichi; Jin, Hidekatsu; Miyoshi, Yasunobu; Fujiwara, Hitoshi (2017)
18th EISCAT symposium Session E7: Space weather and modelling May 26 (Fri), NIPR Auditorium conference object